ANALISA PERBANDINGAN STRUKTUR RANGKA ATAP KAYU DENGAN BAJA RINGAN DARI SEGI KETAHANAN DAN KEGAGALAN KONSTRUKSI - Ikhsan, Muhammad Nur; Endah Purnamasari; Siska Dewi; Januari Yanto; Riski Wahyudi (Universitas Tangerang Raya, 2024)
The roof construction is the highest part of the building. Various problems with roof construction depend on the area to be protected, the shape and construction chosen, and the covering layer. This study aims to study and analyze the structure of wooden roof trusses and light steel roof trusses, study construction failures, find a comparison of construction failures between wooden roof trusses and light steel roof trusses. The method used is the meta-analysis method. The causes of failure that occur due to the use of wood are cracks or breaks, setbacks or corrosion and accidental cracks while the causes of failure in light steel are due to bending and due to curling. The results of the calculation of the 7 x 9 m building obtained the most economical truss trunk dimensions for wood materials are 6 / 8 cm for upper, lower, diagonal and vertical trunks. For the left and right vertical rods use 2 4/10 cm timbers. As for steel materials, it uses a 2L 35x35x4 mm isosceles elbow steel profile for all bars. In a 10 x 15 m building, wooden easels use a size of 8/10 cm for the upper, lower, diagonal and vertical trunks in the middle. For the left and right vertical rods, use 2 4/10 cm sticks. Meanwhile, the steel trusses use 2L 40x40x4 mm isosceles elbow steel profiles for the top rod, 2L 35x35x4 mm for the bottom and vertical rods and 2L 45x45x5 mm for the diagonal rod. From the results of the calculation of the weight of wooden and steel easels, a weight difference of 19% was obtained in the 7 m span and 12.5% in the 10 m span, with wooden easels lighter than steel materials.